Internalisasi Nilai Karakter dalam Pembelajaran PAI Melalui Keteladanan Pendidik - Ardianto (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
The importance of character education is not only limited to the delivery of material on a regular basis but it requires seriousness, tenacity, continuity and habituation carried out by educators of their students. Educators are figures who are idolized by their students, therefore educators should be able to set an example. This research uses literature study by analyzing books, scientific essays, and journals that are relevant to the title. The results of the internalization analysis of character values in PAI learning through teacher modeling are: 1) Internalization of character values by teacher modeling must pay attention to the learning component and maximize all components, especially teachers, in taking various methods that are appropriate for students. 2) teacher modeling is done with attitudes, actions and style of speech. 3) prophetic example.